Different Levels Of Addition Of Salinity To Survival, Growth And Conversion-Efficiency Feed’s Tilapia (Oreochromis sp.) - Agung Setia Abadi (Journal of Aquaculture Development and Environment, 2021)
Tilapia is one of the consumption fish commodities that was very popular with the public. The development of tilapia aquaculture was growing rapidly, especially saline tilapia. The high potential of saline tilapia development causes the demand for fingerlings to increase. This research aimed to determine the best dose of salinity increase in the effort to adapt freshwater tilapia to saline tilapia. In addition, it also observed survival, growth and feed efficiency. The method used was experimental method with completely randomized design and data were analyzed using SPSS16 and Tukey's test. The research treatments included the levels of addition of salinity by 1 ‰/day, 2 ‰/day, 3/day and 4 ‰/day. The difference in salinity had a significant effect on Survival Rate (SR), Growth Rate (GR), Specific Growth Rate (SGR), Feed Conversion Ratio (FCR) and Feed Utilization Efficiency (FUE). The best treatment in this research was the addition of salinity of 1 ‰/day with SR of 96%, GR of 35.1 g / t, SGR 1.22% w / day, FCR of 1.04 and FUE of 96%.